Online-Based MBSR Group Intervention to Reduce Anxiety and Perceived Stress in Scholars Who Work on Undergraduate Thesis - Fionna Gracia; Dini Rahma Bintari (Journal of Educational, Health and Community Psychology, 2023)
Scholars who work on undergraduate thesis are prone to experience anxiety. In addition, the perceived stress of scholars to be able to complete the project is an influential factor in increasing anxiety symptoms in scholars who are working on their thesis. The present study aims to explore the effectiveness of a five-week online-based group intervention using Mindfulness-Based Stress Reduction in reducing anxiety and perceived stress of scholars who work on undergraduate thesis. The study was a pre- and post-test experimental design in which participants were tested for psychological parameters, both before and after the intervention. Participants were divided into 2 groups, treatment and control which consists of eight scholars (seven females and one male). Online intervention consisted of 5 sessions which lasted about 150-200 minutes on each session. Generalized Anxiety Disorder - 7 (GAD-7) and Perceived Stress Scale-10 (PSS-10) was used to measure anxiety and perceived stress, respectively. Statistical analysis indicated that online-based MBSR was not significantly effective in reducing anxiety and perceived stress. However, a trend of positive improvement was observed, indicating the potential benefits of MBSR for reducing anxiety symptoms in scholars who are working on their thesis. Limitations of this study are explained in the discussion section.Keywords: Anxiety, online interventions, mindfulness, perceived stress